2016
DOI: 10.1002/hec.3377
|View full text |Cite
|
Sign up to set email alerts
|

The Effect on Mental Health of Retiring During the Economic Crisis

Abstract: T his paper investigates the causal im pact of retirem ent on late life depression, a grow ing concern for public health as m ajor depressive disorders are the second leading cause of disability. W e shed light on the role of econom ic conditions in shaping the effect of retirem ent on m ental health by exploiting the tim e and regional variation in the severity of the econom ic crisis across ten E uropean countries over the 2004 -2013 period. W e use data from four w aves of the Survey of H ealth, A geing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 27 publications
6
55
0
3
Order By: Relevance
“…Our results indicate that delaying pension claiming could be a risk factor for cardiovascular health, as it is associated with an increase in the incidence of CVD hospitalization by approximately 21 percent. Consistently with previous works assessing the impact of retirement on different health outcomes (Belloni, Meschi, and Pasini 2016;Carrino, Glaser, and Avendano 2018;Dayaram and McGuire 2019;Kolodziej and Garcia-Gomez 2019;Mazzonna and Peracchi 2017;Westerlund et al 2009), we have found evidence of substantial heterogeneity depending on the previous occupation and health status. In fact, the detrimental effect of delaying pension age is borne by retirees previously employed in low-skilled and more physically demanding jobs and by those with worst health at baseline, while we find a null effect among retirees previously employed in occupations offering better conditions or enjoying better health.…”
Section: Discussionsupporting
confidence: 91%
“…Our results indicate that delaying pension claiming could be a risk factor for cardiovascular health, as it is associated with an increase in the incidence of CVD hospitalization by approximately 21 percent. Consistently with previous works assessing the impact of retirement on different health outcomes (Belloni, Meschi, and Pasini 2016;Carrino, Glaser, and Avendano 2018;Dayaram and McGuire 2019;Kolodziej and Garcia-Gomez 2019;Mazzonna and Peracchi 2017;Westerlund et al 2009), we have found evidence of substantial heterogeneity depending on the previous occupation and health status. In fact, the detrimental effect of delaying pension age is borne by retirees previously employed in low-skilled and more physically demanding jobs and by those with worst health at baseline, while we find a null effect among retirees previously employed in occupations offering better conditions or enjoying better health.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we have not paid any attention to retirement in this review, which also could be considered a drawback. Belloni et al 104 have e.g. shown that retirement improves mental health among blue-collar, but not among whitecollar workers.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Further, as often the onset is at an early age and episodes recur, it is considered a leading cause of Years Lived with Disability (Friedrich, 2017;WHO, 2017a), where its relative contribution over the past 25 years has been increasing (Ferrari et al, 2013). Research has shown that it is prevalent among older persons and it is strongly related to an increase in morbidity and mortality (Beekman et al, 1999;Schultz et al, 2000;Turvey et al, 2009); it is also linked to a decline in quality of life and heavy utilisation of health-care services (D'Alisa et al, 2006;Belloni et al, 2016). As the numbers of persons aged 60 or higher are projected to increase substantially in the future (WHO, 2017b), pinpointing factors affecting their health and wellbeing becomes of ever-increasing importance, especially in Europe where the ageing process is more advanced compared to the other regions of the world.…”
Section: Introductionmentioning
confidence: 99%